1992
DOI: 10.1254/jjp.60.187
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Antinephritic Effects of Plant Components (6): Antinephritic Effects and Mechanisms of Phellodendrine (OB-5) on Crescentic-Type Anti-GBM Nephritis in Rats (2).

Abstract: ABSTRACT-Effects of phellodendrine (OB-5) on crescentic-type anti-GBM nephritis in rats and the cell number of the various leukocyte subpopulations in the glomeruli of the nephritic rats were investi gated. OB-5 at 25, 50 and 100 mg/kg/day, p.o. prevented the urinary protein excretion by the 19th day after i.v.-injection of anti-GBM serum. In the OB-5-treated rats, plasma cholesterol and creatinine con tents were lower than those of the control rats throughout the 40-day experimental period. Histopatho logical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Renal tissues for immunoperoxidase staining were fixed in paraformaldehyde-lysine-periodate, and serial cryostat sections (4 pm) were labeled with monoclonal antibodies (mAbs) as previously reported (9). The monoclonal antibodies used in this study were as follows: OX-1 (leukocyte common antigen, total leukocyte), W3/25 (CD4, helper/inducer T cells), OX-8 (CD8, cytotoxic/suppressor T cells), ED-1 (most macrophage and some dendritic cells), OX-39 (interleukin-2 (IL-2) receptor, activated T cells) and OX-18 (MHC class II, la positive cell).…”
Section: Analysis Of Glomerular Leukocyte Accumulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Renal tissues for immunoperoxidase staining were fixed in paraformaldehyde-lysine-periodate, and serial cryostat sections (4 pm) were labeled with monoclonal antibodies (mAbs) as previously reported (9). The monoclonal antibodies used in this study were as follows: OX-1 (leukocyte common antigen, total leukocyte), W3/25 (CD4, helper/inducer T cells), OX-8 (CD8, cytotoxic/suppressor T cells), ED-1 (most macrophage and some dendritic cells), OX-39 (interleukin-2 (IL-2) receptor, activated T cells) and OX-18 (MHC class II, la positive cell).…”
Section: Analysis Of Glomerular Leukocyte Accumulationmentioning
confidence: 99%
“…Labeling cryostat tissue sections with each mAbs were analyzed as regards to the number of cells in the leukocyte subpopula tion in the glomeruli. Cells labeled by each of the mAbs within each glomerulus were counted with an image analyzer (Toyobo Image analyzer V1, Toyobo Co., Ltd., Tokyo), and the results were expressed as the number of cells per glomerular cross section (9).…”
Section: Analysis Of Glomerular Leukocyte Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Neild et al (6) reported that suppression of T cell function by cyclosporin A (CyA) blocked the subse quent development of glomerular lesions in acute sickness nephritis. We reported that mizoribin (7), azathioprine (7), CyA (8), methylprednisolone (9) and some plant com ponents (10) that have immunosuppressive action showed a salutary effect on anti-GBM nephritis. Although these immunosuppressive agents exert antinephritic action, it is difficult to use them in clinical trials because of their side effects (11).…”
mentioning
confidence: 99%
“…There is evidence that glucocorticoids inhibit IL-2 and IL-10 production stimulated by anti-CD3, LPS, or PHA [21, 22]. Moreover, it is known that increases in the IL-2 level in the glomeruli in nephritis induced by heterogeneous antibody injection and suppression of IL-2 function, particularly local suppression in the kidney, lead to improvement of nephritis [23, 24]. The mechanisms by which Th1 cytokines affect the consequent inflammatory cascade that is caused by glomerular injury, such as proteinuria or histopathological changes, remain unclear.…”
Section: Discussionmentioning
confidence: 99%